Structure, regulation, and host interaction of outer membrane protein U (OmpU) of Vibrio species. (January 2022) - Ganie, Hilal A.; Choudhary, Aaina; Baranwal, Somesh
Abstract: OmpU is a multimeric, cation selective outer membrane protein of Vibrio and related species that non-covalently interact with peptidoglycan layer. Interaction of OmpU with human host cells triggers signaling pathways to promote cytokine secretion, reactive oxygen species production, and caspase independent death in immune and epithelial cells. Non-choleric OmpU imparts resistance to antimicrobial peptides and induces actin cytoskeletal reorganization in the host cells. Further, OmpU isolated from Vibrio species elicits an immune response in several aquaculture hosts. Importantly, in-vivo studies using recombinant OmpU or OmpU derived mimotopes reveal a short-lasting immunity, and protection against Vibrio in the aquaculture sector. In conclusion, OmpU is a key adhesion protein and an important virulence factor for successful colonization of Vibrio species into hosts. This review article provides a broad overview of structural, regulatory, and functional mechanisms of OmpU in normal and disease states. Highlights: ● O uter M embrane P roteins (OMPs) are important adhesion factors that play a role in host colonization and evasion of host defense. ● OmpU, the most abundant and conserved outer membrane protein among Vibrio species, induces proinflammatory response and apoptosis in host cells. ● OmpU activates receptor-mediated pathways in several target cells and enters the cell via clathrin dependent endocytosis. ● OmpU, a strong immunogen, has a potential to protect non-choleric infection in the aquaculture sector.